Government Control vs Market Mechanism in the Land Use Market in Human Settlement Development - Achmad Nurmandi, Nugroho Trisusanto (the Korean Association for Public Administratio, 2013)
Structure plans have been used in Indonesia since the 1960s and applied throughout the regency or municipality and the province as one form of landuse control, particularly for private land development, to sustain water conservation. Sleman Regency issued Regulation No. 23 of 1994, an instrument designed to control massive private land development for housing projects. Furthermore, to control land development because of the expansion of the city, the local government established the Office of Land Control Areas (DPPD). This study aims to investigate the state’s capacity to control land conversion for development through licensing mechanisms, particularly land conversionfrom wetland /paddy fields to non-paddy fields. Trend analysis and gap analysis using geographic information system (GIS) data are used to evaluate differences between developmental plans and actual land conversion. The results of this study onthe conversion of village land for rivate housing projects from years 2006-2008 found that 550.05 ha of land has been c onverted, but only 236 ha of land was converted through the permit process.